Current research status of intense pulsed light for melasma - Hongxin WANG; Wenlong FAN; Xiaoyu YANG; Dongyu CHEN; Yuqing HE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
In recent years, intense pulsed light (IPL) has been widely used in clinical practice and has made great progress in the treatment of melasma. Since multiple mechanisms are involved in the pathogenesis of melasma, at the present time, IPL is often used clinically as a comprehensive treatment according to different etiologies, with remarkable efficacy, high safety and good patient compliance. Therefore, here we review the research progress of IPL in the treatment of melasma.